ISLAMIC EDUCATION SYSTEM AND CHARACTER EDUCATION AT INTEGRAL ELEMENTARY SCHOOL OF LUQMAN HAKIM BOJONEGORO - Siti Ermawati (Jurnal Pendidikan Edutama, 2018)
This research was conducted at Integral Elementary School of Luqman Hakim Bojonegoro by analyzing its Islamic education system and its implementation in building the students’ characters. It employed qualitative approach by descriptive method in a case study type. The data were collected through interview and documentation using method and source triangulation as data validity test. The data analysis technique was interactive analysis method. The research results showed that (1) the Islamic education system applied at this school was combining diniyah and academic achievement. This elementary school emphasizes on Al Qur’an and science, (2) the implementation of Islamic education in building the students’ characters is actualized in the classroom learning activity (combining Al Qur’an and science), the teachers’ exemplary in educating the students during the teaching process both inside and outside the classroom, one of which is by having extracurricular that implementing the character education values.  Keywords: Islamic Education System, Character Education. Abstrak Penelitian ini bertujuan untuk menganalisis sistem pendidikan Islam dan implementasinya dalam membentuk karakter siswa pada SD Integral Luqman Hakim Bojonegoro. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, sedangkan jenis penelitian ini adalah studi kasus. Pengumpulan data penelitian dilakukan melalui wawancara dan dokumentasi. Uji validitas data yang digunakan adalah trianggulasi metode dan trianggulasi sumber. Sementara itu, teknik analisis data yang digunakan adalah metode analisis interaktif. Hasil penelitian menunjukkan bahwa (1), Sistem pendidikan Islam yang diterapkan di SD Integral Luqman Hakim, yakni dengan memadukan pendidikan Islam yang unggul dalam diniyah dan unggul dalam akademik, SD Integral luqman hakim mengedepankan pembelajaran yang berbasis Al-qur’an dan sains (2) Implementasi pendidikan Islam dalam membentuk karakter siswa di SD Integral luqman hakim terwujud dalam kegiatan pembelajaran dikelas (perpaduan Al-qur’an dan sains), serta keteladanan pengajar dalam mendidik siswa – siswi yang tidak ada diwujudkan dalam pembelajaran di dalam kelas dan diluar kelas, misalnya seperti ekstrakulikuker yang mengimplentasi nilai-nilai pendidikan karakter.Kata Kunci: Sistem, Pendidikan, Karakter